Um Jardim Chamado Brasil:percalços do nacional e do moderno no romance contemporâneo - Aguiar, Denise Brasil Alvarenga (2006)
This thesis carries out the study of representations of national in contemporary Brazilian novel, mainly approaching with the insertion of such literary phenomenon in the general questions related to modernity and its crisis. The debate of the relations between fictional word and building of national identity if still linked to some of main dilemmas, which are presented at Brazil s history, in its affirmation as political and social being, as well as into the representations, which were able to awake into cultural imaginary. As a central corpus by exposing some of main patterns of the experience which was set up by modernity in Brazilian art and society, this work analyses the novel from Ronaldo Lima Lins, Jardim Brasil: conto.